2005
DOI: 10.1002/cncr.21369
|View full text |Cite
|
Sign up to set email alerts
|

Resection of recurrent pulmonary metastases in patients with osteosarcoma

Abstract: BACKGROUNDSurgical resection of lung metastases is widely accepted in osteosarcoma patients. Few data exist on treatment of recurrent pulmonary metastases. The authors of the current study retrospectively analyzed patients with osteosarcoma who received surgery for recurrent lung metastases.METHODSFrom 1980 to 2001, 127 metastasectomies were performed on 94 patients. Criteria of eligibility were no metastases beyond the lung, no local recurrence, possibility of achieving complete resection of metastases withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 59 publications
3
88
0
2
Order By: Relevance
“…In a previous systematic review of reported outcome in approximately 1,800 osteosarcoma patients with pulmonary metastases from 1939 to 2007, the main prognostic factor affecting survival was found to be complete surgical remission [1,[4][5][6]8]. In addition, DFI, as well as number and localization of metastases, has also been found to be significantly associated with survival [3,[5][6][7][9][10][11].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous systematic review of reported outcome in approximately 1,800 osteosarcoma patients with pulmonary metastases from 1939 to 2007, the main prognostic factor affecting survival was found to be complete surgical remission [1,[4][5][6]8]. In addition, DFI, as well as number and localization of metastases, has also been found to be significantly associated with survival [3,[5][6][7][9][10][11].…”
Section: Discussionmentioning
confidence: 97%
“…The number of metastases has been a matter of interest since the study by Putnam et al who described an association between decreased survival and more than three metastases on preoperative CT [12]. However, most studies do not describe how the cut-off point for the number of nodules was determined, and therefore cut-offs range between "more than one" and "six nodules or more" [1][2][3][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…3,5,7,13,15,17,18,19 : 1. Autologous bone graft: This form of graft has no rejection and a low rate of infection.…”
Section: © the Foot And Ankle Online Journal 2010mentioning
confidence: 99%
“…However, in the last two decades, the overall survival of OS patients with local disease has plateaued 4,5 . Moreover, 30-40% of these patients relapse within 3 years after diagnosis and patients with metastatic disease continue to have a poor survival of 20-30% 4,6,7 . To improve the outcome of these patients, new therapeutic strategies need to be developed.…”
Section: Introductionmentioning
confidence: 99%